A comprehensive analysis of academic performance, self-confidence, motivation, and communication in calculus courses: Insights from international and local students - Ramadoni; Tai Chien Kao; Hafizah Delyana; Anna Cesaria; Arie Purwa Kusuma (Jurnal Elemen, 2025)
Taiwan's rapid development in education is evidenced by its high ranking in the 2022 PISA assessment, making it an attractive destination for international students. National Dong Hwa University, particularly its Department of Computer Science and Information Engineering (CSIE), has become popular among these students. This study focuses on the impact of integrating local and international students in calculus courses, a required subject, due to the close relationship between mathematics and computer science. The study sampled 14 international and 14 local first-year students, collecting data through questionnaires to assess their self-confidence, communication skills, and motivation. At the same time, academic performance was measured through midterm exam scores. The findings revealed significant differences in academic performance, self-confidence, and communication between local and international students, with p-values of .024*, .016*, and .012*, respectively. Among international students, self-confidence and communication were significantly correlated with academic performance (p=.013* and p=.026*), while for local students, a significant relationship was found between scores and communication (p=.035*).